PERANAN FORUM KERUKUNAN UMAT BERAGAMA DALAM MEMBINA KERUKUNAN UMAT BERAGAMA DI KOTA BENGKULU - Syahril Syahril (Manthiq, 2017)
Abstract: This study raised the issue of the role of religious harmony forum and enabling and inhibiting factors in fostering religious harmony in the city of Bengkulu. From the results of this study indicate that there has been dialogue,  socialization Joint Regulation  of the Minister, gave a written recommendation on the request for the establishment of houses of worship,  fostering  inter-religious  harmony, internal  religious  communities and religious groups  and the government. But success in fostering religious harmony is still far from expectations and can be said to be ineffective, it can be seen still rarely do inter-religious  dialogue,  no socialization laws on religious harmony to society, there  has been no specific action  in order  the house of worship  that no permit. Supporting factors in fostering religious harmony awareness, motivation,  mutual  understanding and tolerance between religious communities, the support  of the Mayor by providing secretariat building facilities. While the limiting factor in fostering  religious harmony in the city of Bengkulu  is the infrastructure is not yet complete, the  attitude  of religious  communities to theology,  the  political interests that carry the  name of religion, and attitudes toward religious fanaticism.